2010
DOI: 10.1111/j.1365-2230.2009.03523.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum T helper 1 cytokine levels are greater in patients with alopecia areata regardless of severity or atopy

Abstract: Increased Th1 serum cytokines (IL-2, IL-12 and interferon-gamma) and IL-1ra levels are associated with AA regardless of disease severity or the presence of atopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 25 publications
8
85
3
3
Order By: Relevance
“…In contrast, IFN-γ can induce collapse of hair follicle immune privilege [17]. Increased levels of Th1 serum cytokines (IL-2, IL-12 and IFN-γ) are present in patients with AA [19]. Significantly elevated levels of serum IFN-γ have been noticed in patients with alopecia universalis and alopecia totalis compared with patients with single or multiple patchy AA [20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IFN-γ can induce collapse of hair follicle immune privilege [17]. Increased levels of Th1 serum cytokines (IL-2, IL-12 and IFN-γ) are present in patients with AA [19]. Significantly elevated levels of serum IFN-γ have been noticed in patients with alopecia universalis and alopecia totalis compared with patients with single or multiple patchy AA [20].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers stated that these findings could be interpreted as an indication that Th1-type cytokines might be critical for progression to the extensive form and that Th2-type cytokines may exert a more subtle influence of a cell-mediated attack on hair follicles. Barahmani et al [19] analyzed the serum cytokine profiles in 269 patients with AA and found that increased IL-2 levels were associated with AA regardless of the disease severity. Their study suggests that there is a Th1 response early in the disease, as patients with transient AA had higher serum IL-2 levels than patients with longer duration of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated expression of IL-12 has been found in skin lesions from patients with alopecia areata and C3H / HeJ AA mice. 6 Another cytokine of the IL-12 family is IL-23. IL-23 shares with IL-12 the p40 subunit.…”
Section: Discussionmentioning
confidence: 99%